2001
DOI: 10.1080/003655901750170407
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Isolation: Prevalence and the Effect on Well-being among 50-80-Year-Old Prostate Cancer Patients

Abstract: Scand J Urol Nephrol 35: 97-101, 2001Objective: To investigate to what extent prostate cancer patients con de their emotional concerns, and whether having no one to con de in affects well-being. Material and methods: A population-based study using epidemiological methods. A questionnaire was mailed to all 431 living prostate cancer patients aged 50-80 at the time of selection, diagnosed 1.5-2 years previously in Stockholm County, and 435 randomly selected men in the same age group. The questionnaire was comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…One possible explanation may be that younger generations of Icelandic men may find it easier to confront and discuss emotionally taxing feelings. This would be consistent with studies from Sweden, which reported prevalence of emotional isolation among middle-aged and elderly men [24]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…One possible explanation may be that younger generations of Icelandic men may find it easier to confront and discuss emotionally taxing feelings. This would be consistent with studies from Sweden, which reported prevalence of emotional isolation among middle-aged and elderly men [24]. …”
Section: Discussionsupporting
confidence: 93%
“…It remains to be seen in future surveys if widows share the same obstacles as widowers regarding participation in such studies. Research on gender differences indicates that women may be more open regarding the sharing of emotionally taxing feelings and more willing to accept assistance in crisis situations [24,26]. …”
Section: Discussionmentioning
confidence: 99%
“…Possible mechanisms remain unknown but the emotional shock caused by the diagnosis, anxiety for the pending choice of treatment, together with emotional isolation, may explain the impulsive action. About 20% of the prostate cancer patients were reported as having no one to confide in [20].…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have addressed the question of factors influencing TURP bleeding [3, 4, 5, 6, 7, 8, 9, 10]. Each study usually addressed a few factors (usually 2–5), and different studies used different methods of blood estimation, making comparison of studies or extrapolation of results difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Operative blood loss was measured by the method described by Lyrdal and Neidhardt [10]. Briefly, the effluent irrigation fluid during resection was collected in buckets containing 4 litres of water and 20 ml of saponin (20 g dissolved in 100 ml of water) and stirred constantly.…”
Section: Methodsmentioning
confidence: 99%